Anomie and social crisis in Peru off the bicentennial - Caycho Caja, Aaron (2021)
The social crisis caused by the SARS-CoV-2 pandemic has accelerated the pre-existing conditions in the society and enforces quick structural changes. In this context, anomie is described as a phenomenon adjacent to the pandemic and visible in the absence of norms that regulate social patterns. The aim of the present paper is to identify the circumstances preceding the emergence of the anomie in a political context stirred by the last 5 years of corruption. Moreover, we underline the characteristics that allow us to distinguish social anomie in the context of the current crisis. Subsequently, we point out its implications in the labor sector and how it manifested itself in the participation of civil society in the marches of the previous year. In addition, the subjective sense of the individual anomie is explained from a psychological point of view. The essay concludes by suggesting the possibility of social reorganization under the current conditions of social uncertainty.